2013
DOI: 10.1055/s-0033-1359734
|View full text |Cite
|
Sign up to set email alerts
|

Challenges in Interventional Radiology: The Pregnant Patient

Abstract: A pregnant patient presenting to interventional radiology (IR) has a different set of needs from any other patient requiring a procedure. Often, the patient's care can be in direct conflict with the growth and development of the fetus, whether it be optimal fluoroscopic imaging, adequate sedation of the mother, or the timing of the needed procedure. Despite the additional risks and complexities associated with pregnancy, IR procedures can be performed safely for the pregnant patient with knowledge of the speci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(11 citation statements)
references
References 53 publications
0
11
0
Order By: Relevance
“…Neurointerventionalists should have a low threshold for consulting an anesthesiologist, especially for more complex cases, agitated patients, and/or for highrisk pregnancies. 96 Iodinated contrast is a category B medication, and animal studies have not reported teratogenic or mutagenic effects from exposure. Human studies have not demonstrated any inhibitory effect of free iodide on neonatal thyroid gland function.…”
Section: Pregnancymentioning
confidence: 99%
“…Neurointerventionalists should have a low threshold for consulting an anesthesiologist, especially for more complex cases, agitated patients, and/or for highrisk pregnancies. 96 Iodinated contrast is a category B medication, and animal studies have not reported teratogenic or mutagenic effects from exposure. Human studies have not demonstrated any inhibitory effect of free iodide on neonatal thyroid gland function.…”
Section: Pregnancymentioning
confidence: 99%
“…Continuous fetal monitoring for fetal wellbeing is needed during the procedures. In general, regional anesthesia is preferred over general anesthesia [ 36 ]. Fluoroscopy, ultrasound, and CT with or without fusion imaging are the conventional modalities for image guidance during IR procedures.…”
Section: Challenges and Role Of Interventional Radiology In Pregnancymentioning
confidence: 99%
“…Where appropriate, such as in high-risk pregnancy and when deep sedation or analgesia are used, continuous foetal monitoring may be employed during the procedure. [ 7 8 ]…”
Section: Challengesmentioning
confidence: 99%